Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
so we already know what x equals, so just plug it in to the other equation
now we have 4(2y+3)-5y=9
from here, just solve
y=-1
let me know if you have anymore questions :)
ps - Idk if you'd need this but x=1 :)
now we have 4(2y+3)-5y=9
from here, just solve
y=-1
let me know if you have anymore questions :)
ps - Idk if you'd need this but x=1 :)
We solve the system by substitution.
x = 2y + 3
4x-5y = 9
Substituting the value of x in equation no. 2 , we have,
4(2y+3) - 5y = 9
8y + 12 - 5y = 9
3y + 12 = 9
3y = 9-12 = -3
thus, 3y = -3
thus, y = -3/3 = -1
thus, y = -1
x = 2y + 3
4x-5y = 9
Substituting the value of x in equation no. 2 , we have,
4(2y+3) - 5y = 9
8y + 12 - 5y = 9
3y + 12 = 9
3y = 9-12 = -3
thus, 3y = -3
thus, y = -3/3 = -1
thus, y = -1
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.